KOMPETENSI TENAGA PENDIDIK PENDIDIKAN NONFORMAL DALAM MEMBANGUN KEMANDIRIAN WARGA BELAJAR - Mustafa Kamil (Jurnal Ilmiah Visi, 2007)
Non-formal education quality will be reached if it is developed by professional and competent nonformal education personnel. Two factors needed by non-formal education personnel in strengthening their professionalism and competencies are the skills and abilities in developing and improving learners’ autonomy. This article discusses (1) the definitions of non-formal learners’ autonomy, (2 ) the roles and tasks of non-formal education personel in performing non-formal learners’ autonomy, and (3) a set of competencies and skill of non-formal education personnel in performing non-formal learners’ autonomy. In conclusion some suggestions to improve the quality of non-formal education personnel presented.